2021
DOI: 10.2478/jeb-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Banking Market Concentration and Bank Efficiency. Evidence from Southern, Eastern and Central Europe

Abstract: The importance of the question about the relationship between concentration and efficiency lies in the fact that banks’ efficiency affects ability to extend loans and ensure financial stability of the banking sector. The study examines this relationship on the example of 150 banks operating between 2005 and 2019 in 11 EU and 8 non-EU countries from the SECE region. The value of profit efficiency was assessed with the stochastic frontier approach, and next regressed with the banking market concentration and ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 71 publications
6
29
0
Order By: Relevance
“…The results are also in line with the results of Dadoukis et al, who indicates that larger banks and those who were better IT equipped in the pre-pandemic period during the first quarters of the pandemic, better maintained their market position, profitability, and financial stability [53]. Additionally, larger banks have more capacity to introduce non-interest services for diversification of income and improvement of profitability [54][55][56][57].…”
Section: Results Of Modelling and Discussionsupporting
confidence: 89%
“…The results are also in line with the results of Dadoukis et al, who indicates that larger banks and those who were better IT equipped in the pre-pandemic period during the first quarters of the pandemic, better maintained their market position, profitability, and financial stability [53]. Additionally, larger banks have more capacity to introduce non-interest services for diversification of income and improvement of profitability [54][55][56][57].…”
Section: Results Of Modelling and Discussionsupporting
confidence: 89%
“…Increased competition can lead to high risk-taking due to reduced market power and the value of bank franchises” (p. 842). Moreover, the rise in the banking market concentration will most likely affect the efficiency of banks’ operations and their ability to finance the economy (Kozak and Wierzbowska 2021 ). This finding is expected to have strong implications for the regulatory authority and decision-makers in the MENA region to set up policies that promote bank efficiency in addition to establishing several regulations related to capital and bank supervision.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“… 3 In a recent study of 150 banks operating in the SECE region, Kozak and Wierzbowska ( 2021 ) report that under the pressure of market competition, “more effective entities take over less effective competitors and then, thanks to the use of economies of scale and scope, reduce operating costs, diversify the product offer and increase profits” (p. 40). …”
mentioning
confidence: 99%
“…There is no doubt that the COVID-19 pandemic and the subsequent economic crisis have changed banks’ profits and risk sources, forcing them to change their business model [ 28 ]. According to Kozak and Wierzbowska [ 1 ], the expected increase in banking market consolidation due to the recent global crisis (COVID-19 pandemic) will most likely affect banks’ efficiency and ability to finance economic development. Moreover, Hamadi and Awdeh [ 29 ] concluded that “per se is not harmful to financial development.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In this paper, we investigate the effect of market concentration on bank efficiency using a sample of 225 banks in the countries in the Middle East and North Africa (MENA) region. According to Kozak and Wierzbowska [ 1 ], the importance of the relationship between banking market concentration and bank efficiency lies in the fact that “bank efficiency affects the ability to extend loans and ensure the financial stability of the entire banking sector” (p. 1). This issue is significant for emerging economies, including those in the MENA region, where financial markets are still underdeveloped, and bank credit is the primary source of financing economic growth.…”
Section: Introductionmentioning
confidence: 99%